Related Articles

# Class 9 RD Sharma Solutions – Chapter 5 Factorisation of Algebraic Expressions- Exercise 5.4

• Last Updated : 28 Mar, 2021

### Question 1. a3 + 8b3 + 64c3 – 24abc

Solution:

We know that

a3 + b3 + c3 – 3abc = (a + b + c) (a2 + b2 + c2 – ab – bc – ca)

= a3 + 8b3 + 64c3 – 24abc

= (a)3 + (2b)3 + (4c)3 – (3 × a × 2b × 4c)

= (a + 2b + 4c) [(a)2 + (2b)2 + (4c)2 -(a × 2b)– (2b × 4c)– (4c × a)]2

= (a + 2b + 4c) (a2 + 4b2 + 16c2 – 2ab – 8bc – 4ca)

### Question 2. x3 – 8y3 + 27z3 + 18xyz

Solution:

We can simplify the given equation as :

x3 – 8y3 + 27z3 + 18xyz

= (x)3 + (-2y)3 + (3z)3 – ( 3 * x * (-2y) * (3 z))

= (x – y + 3z) (x2 + 4y2 + 9z2 + 2xy + 6yz – 3zx)

### Question 3. 27x3 – y3– z3 – 9xyz

Solution:

27x3 – y3 – z3 – 9xyz

= (3x)3 + (-y)3 + (-z)3 – (3 * 3x * (-y) (-z))

= (3x – y – z) [(3x)2 + (-y)2 + (-z)2 – (3x * (-y)) – ((-y) (-z))- (- z × 3x)]

= (3x – y – z) (9x2 + y2 + z2 + 3xy – yz + 3zx)

### Question 4. (1/27)x3 – y3 + 125z3 + 5xyz

Solution:

=(1/3x)3 + -(y)3 +(5z)3 – 3*(1/3x) * (-y) * (5z)

=((1/3x) – y +5z)[(1/3x)2 + (-y)2 + (5z)2 -((1/3x)*-y) – (-y * 5z) – (5z * (1/3x))

=((1/3x) – y +5z)[(1/9)x2 + y2 +25z2 + (1/3xy) + 5yz – (5/3xz)]

### Question 5. 8x3 + 27y3 – 216z3 + 108xyz

Solution:

8x3 + 27y3 – 216z3 + 108xyz

= (2x)3 + (3y)3 + (6z)3 – 3 × (2x) (3y) (-6z)

= (2x + 3y – 6z) [(2x)2 + (3y)2 + (-6z)2 – (2x * 3y) – (3y * (-6z)) – ((-6z) * 2x)]

= (2x + 3y – 6z) (4x2 + 9y2 + 36z2 – 6xy + 18yz + 12zx)

### Question 6. 125 + 8x3 – 27y3 + 90xy

Solution:

125 + 8X3 – 27y3 + 90xy

= (5)3 + (2x)3 + (-3y)3 – [3 * 5 * 2x * (-3y)]

= (5 + 2x – 3y) [(5)2 + (2x)2 + (-3y)2 – (5 * 2x) – (2x * (-3y)) – ((-3y) * 5)]

= (5 + 2x – 3y) (25 + 4x2 + 9y2– 10x + 6xy + 15y)

### Question 7. 8x3 – 125y3 + 180xy + 216

Solution:

8x3 – 125y3 + 180xy + 216

= (2x)3 + (-5y)3 + (6)3 – 3 * 2x *(-5y) * 6

= (2x – 5y + 6) [(2x)2 + (-5y)2 + (6)2 – 2x *(-5y) – (-5y) * 6 – 6 * 2x]

= (2x – 5y + 6) (4x2 + 25y2 + 36 + 10xy + 30y – 12x)

### Question 8. Multiply:

(i) x2 +y2 + z2 – xy + xz + yz by x + y – z

(ii) x2 + 4y2 + z2 + 2xy + xz – 2yz by x- 2y-z

(iii) x2 + 4y2 + 2xy – 3x + 6y + 9 by x – 2y + 3

(iv) 9x2 + 25y2 + 15xy + 12x – 20y + 16 by 3x – 5y + 4

Solution:

(i) (x2 + y2 + z2 – xy + yz + zx) by (x + y – z)

= x3 +y3 – z3 + 3xyz

(ii) (x2 + 4y2 + z2 + 2xy + xz – 2yz) by (x – 2y – z)

= (x -2y-z) [x2 + (-2y)2 + (-z)2 – (x * (- 2y)) – ((-2y)* (z)) – ((-z) (x))]

= x3 + (-2y)3 + (-z)3 – 3x * (-2y) * (-z)

= x3 – 8y3 – z3 – 6xyz

(iii) x2 + 4y2 + 2xy – 3x + 6y + 9 by  (x – 2y + 3)

= (x – 2y + 3) (x2 + 4y2 + 9 + 2xy + 6y – 3x)

= (x)3 + (-2y)3 + (3)3 – (3 * x * (-2y) x 3)

= x3 – 8y3 + 27 + 18xy

(iv) 9x2 + 25y2 + 15xy + 12x – 20y + 16 by (3x – 5y + 4)

= (3x -5y + 4) [(3x)2 + (-5y)2 + (4)2 – 3x * (-5y) +(-5y x 4) + (4 × 3x)]

= (3x)3 + (-5y)3 + (4)3 – 3 * 3x *(-5y) * 4

= 27x3 – 125y3 + 64 + 180xy

### Question 9. (3x – 2y)3 + (2y – 4z)3 + (4z – 3x)3

Solution:

(3x – 2y)3 + (2y – 4z)3 + (4z – 3x)3

∵ 3x – 2y + 2y – 4z + 4z – 3x = 0

∴ (3x – 2y)3 + (2y – 4z)3 + (4z – 3x)3

= 3(3x – 2y) (2y – 4z) (4z – 3x)               {∵ x3 + y3 + z3 = 3xyz if x + y + z = 0}

### Question 10. (2x – 3y)3 + (4z – 2x)3 + (3y – 4z)3

Solution:

(2x – 3y)3 + (4z – 2x)3 + (3y – 4z)3

∵ 2x – 3y + 4z – 2x + 3y – 4z = 0

∴ (2x – 3y)3 + (4z – 2x)3 + (3y – 4z)3

= 3(2x – 3y) (4z – 2x) (3y – 4z)                {∵ x3 + y3 + z3 = 3xyz if x + y + z = 0}

### Question 11. [(x/2)+y +(z/3)]3 + [(x/3) -(2y/3) +z]3 + [(-5x/6)-(y/3)-(4z/3)]3

Solution:

[(x/2)+y +(z/3)]3 + [(x/3) -(2y/3) +z]3 + [(-5x/6)-(y/3)-(4z/3)]3

∵ (x/2) + y +(z/3) +(x/3) -(2y/3) + z – (5x/6) -(y/3) – (4z/3) =0

∴ [(x/2)+y +(z/3)]3 + [(x/3) -(2y/3) +z]3 + [(-5x/6)-(y/3)-(4z/3)]3

= 3[(x/2)+y +(z/3)] [(x/3) -(2y/3) +z] [(-5x/6)-(y/3)-(4z/3)]     {∵ a3 + b3 + c3 = 3abc if a + b + c = 0}

### Question 12. (a – 3b)3 + (3b – c)3 + (c – a)3

Solution:

(a- 3b)3 + (3b – c)3 + (c – a)3

∵ a – 3b + 3b – c + c – a = 0

∴ (a – 3b)3 + (3b – c)3 + (c – a)3

= 3(a – 3b) (3b – c) (c – a)                       {∵ a3 + b3 + c3 = 3abc if a + b + c = 0}

### Question 13. 2√2a3 + 3√3b3 + c3 – 3√6abc

Solution:

= (√2a)3 +(√3b)3 +c3 – 3 * √2a * √3b * c

= (√2a + √3b +c)[(√2a)2 +(√3b)2 + c2 – (√2a * √3b) – (√3b * c) – (c * √2a)

= (√2a + √3b +c)(2a2 + 3b2 + c2 – √6ab – √3bc – √2ca)

### Question 14. 3√3a3 – b3 – 5√5c3 – 3√15abc

Solution:

= (√3a)3 + (-b)3 +(-√5c)3 – 3*√3a* (-b) *(-√5c)

= (√3a – b – √5c) [(√3a)2 + (-b)2 +(-√5c)2 – (√3a* -b) – (-b * (-√5c)) – (-√5c* √3a)

= (√3a – b – √5c)(3a2 + b2 + 5c2 + √3ab – √5bc + √15ca)

### Question 15. 2√2 a3  + 16√2 b3 + c3 – 12abc

Solution:

=(√2a)3 + (2√2b)3 + c3 – (3 * √2a * 2√2b * c)

=(√2a + 2√2b +c) [(√2a)2 + (2√2b)2 + c2 – (√2a* 2√2b) – (2√2b*c) – (c* √2a)

=(√2a + 2√2b +c)[2a2 + 8b2 + c2 – 4ab – 2√2bc – √2ca]

### Question 16. Find the value of x3 + y3 – 12xy + 64, when x + y = – 4

Solution:

x3 + y3 – 12xy + 64

x + y = -4

On Cubing both sides,

x3 + y3 + 3 xy(x + y) = -64

Substitute the value of (x + y)

⇒ x3 + y3 + 3xy * (-4) = -64

⇒ x3 + y3 – 12xy + 64 = 0

Attention reader! All those who say programming isn’t for kids, just haven’t met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12.

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

My Personal Notes arrow_drop_up